ACTIVITY BASED COSTING (ABC) SEBAGAI PENDEKATAN BARU UNTUK MENGHITUNG ANALISIS STANDAR BELANJA (ASB) DALAM PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DAERAH (APBD) - Sri Fadilah (Program Magister Akuntansi Unsyiah, 2009)
The system covers all areas of financial accounting activities related to the budget. Therefore, all transactions in the local government should be an adequate bookkeeping system as a supporter of regional financial accountability, until the published financial statements. Standard analysis of expenditures / costs originated from the direction of public policy and government budgets are then developed in the strategy and priority development programs and activities that have defined the local government. Furthermore, Standard Analysis Expenditure (ASB) is a standard or guideline that is used to analyze the reasonableness of the workload or cost of any program or activity conducted in a budget year. Assessment of the ASB budget includes two things: fairness, reasonableness of workload and cost. One approach that can be used to assess the reasonableness of the standard expenditure analysis is Activity Based Costing (ABC). Activity Based Costing (ABC) is the pricing of goods or the cost of the activity based budget. This means that a trigger activity costs (cost drivers) in the approach to Activity Based Costing (ABC's). Approach Activity Based Costing (ABC) is a technique for quantitatively measuring costs and performance of an activity (the cost and performance of activities) and the allocation of resources and costs, whether by operation and by administrative personnel. It is expected that using Activity Based Costing (ABC) in determining the standard analysis of expenditure will be prepared budget revenues and government spending (budget) in an efficient and effective. Keywords: Standard Analysis Expenditure (ASB), Activity Based Costing (ABC) and Local Expenditures Budget (Budget)